Advances in raw material industries for sustainable development goals : proceedings of the XII Russian-German Raw Materials Conference (Saint-Petersburg, Russia, 27-29 November 2019) /: proceedings of the XII Russian-German Raw Materials Conference (Saint-Petersburg, Russia, 27-29 November 2019). (2020) - Unknown
No abstract available